2009
DOI: 10.1371/journal.pone.0005883
|View full text |Cite
|
Sign up to set email alerts
|

General Intelligence in Another Primate: Individual Differences across Cognitive Task Performance in a New World Monkey (Saguinus oedipus)

Abstract: BackgroundIndividual differences in human cognitive abilities show consistently positive correlations across diverse domains, providing the basis for the trait of “general intelligence” (g). At present, little is known about the evolution of g, in part because most comparative studies focus on rodents or on differences across higher-level taxa. What is needed, therefore, are experiments targeting nonhuman primates, focusing on individual differences within a single species, using a broad battery of tasks. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 35 publications
4
63
1
Order By: Relevance
“…They have also found that this general cognitive performance is correlated quite strongly with brain size, corrected slightly for the effects of body size [25,26]. Similar intraspecific studies on cotton-top tamarins (Saguinus oedipus) support the notion of general intelligence [81], whereas results on chimpanzees also agree if we accept the finding [82] that spatial cognition is on a separate dimension. Domain-general cognitive abilities may be even more widespread in the animal kingdom and also occur in other mammals and birds [83][84][85].…”
Section: Box 2 General Intelligence In Nonhumanssupporting
confidence: 56%
“…They have also found that this general cognitive performance is correlated quite strongly with brain size, corrected slightly for the effects of body size [25,26]. Similar intraspecific studies on cotton-top tamarins (Saguinus oedipus) support the notion of general intelligence [81], whereas results on chimpanzees also agree if we accept the finding [82] that spatial cognition is on a separate dimension. Domain-general cognitive abilities may be even more widespread in the animal kingdom and also occur in other mammals and birds [83][84][85].…”
Section: Box 2 General Intelligence In Nonhumanssupporting
confidence: 56%
“…To address this question in Experiment 2, we compared the same species from Experiment 1 on a nonsocial task measuring inhibitory control. If the cognitive differences we observed in Experiment 1 reflect domain-general cognitive differences between species [48,49] we predicted that we should observe the same relationship between group size and performance in a second nonsocial cognitive task. However, if the species differences from Experiment 1 are specific to social cognition [21], we predicted that performance on a nonsocial cognitive task would not bear the same relationship with a species' typical group size.…”
Section: Methodsmentioning
confidence: 79%
“…However, we note that Johnson et al (2002) did not find strong evidence of genus*domain interactions in their meta-analysis of primate cognition (though genus effects were included), although Banerjee et al (2009), using rank data analyses similar to those proposed in Johnson et al (2002), did report evidence of genus*domain interactions. While it is difficult to identify the exact nature of these seemingly contradictory finding, there are several possible explanations.…”
Section: Discussionmentioning
confidence: 63%
“…Most importantly, however, is the manner in which data were collected. Data reported in Johnson et al (2002) were based on an historical meta-analysis of data collected over 70 years from multiple researchers, whereas data analyzed here and in Banerjee et al (2009) were collected under more controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation